The Character Education Management in Realizing Graduate Quality - Makky, Muhammad; Aan Hasanah; Mahrus As'ad; Ara Hidayat; Faiq Aliyev (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
One persistent challenge in Indonesian education is the insufficient internalization of character values among students, which can affect the overall quality of graduates. This study aims to explore the management of character education in enhancing graduate quality at Al-Ittihad Senior High School Cianjur and Ciranjang 1 Public Senior High School. The research adopts a qualitative approach using a multi-case study design. Data were collected through in-depth interviews, participatory observation, and document analysis to obtain a comprehensive understanding of character education practices in both institutions. The findings indicate that both schools emphasize the development of strong academic character and religious or moral awareness, although through different approaches. Al-Ittihad Senior High School integrates the national curriculum with Islamic boarding school values through boarding programs, structured worship routines, and daily religious habits. In contrast, Ciranjang 1 Public Senior High School implements character education based on its BIJAK’S vision, which is embedded in intracurricular and extracurricular activities as well as positive daily habits. Organizationally, Al-Ittihad involves close collaboration between the principal, teachers, and boarding school supervisors, while Ciranjang 1 relies more on a formal public school structure, with the vice principal for student affairs and supervising teachers playing key roles. Implementation at Al-Ittihad is centered on boarding school life, whereas Ciranjang 1 focuses on the BIJAK’S program emphasizing discipline, achievement, creativity, and entrepreneurship. Supervision and evaluation at Al-Ittihad are conducted intensively by teachers, dormitory supervisors, and parents, while Ciranjang 1 applies regular teacher meetings, program evaluations, and parental involvement to monitor character development.